UJI PENGGUNAAN LIMBAH CAIR BIOGAS DAN PUPUK N, P, K TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L) - Semeon Panjaitan; Idwar '; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Cacao is a commodity plantation crops of high economic value and potential as a foreign exchange earner of the country. Planting medium is one of the factors that affect the growth of the cacao plants in the nursery, so we need organic fertilizer and inorganic fertilizer. The objective of this study to know the effect of bioslurry fertilizerand fertilizer N, P, K and interaction both on the growth of seedlings of cacao (Theobroma cacao L). Research conducted at the experimental field of the Faculty of Agriculture, University of Riau, from January until the month of April 2015. This research was conducted by using aCompletely Randomized Design (CRD) factorial, the first factor is the bioslurry fertilizerwith 4 levels (0, 50, 100 and 150) ml/ seedling and the second factor is N, P2O5, K2O with 4 levels (0, 1, 2, and 3) g/ seedling. The combination is repeated 3 times so that there are 48 units of trial and each experimental unit consists of 4 plants, so the total is 192 plants. Parameters measured were seedling height (cm), number of leaves (pieces), stem circumference (cm), root volume (ml), leaf area (cm2 ), dry weight (g), and the ratio of root and crown and root dry weight. Statistical analysis using analysis of variance followed by Duncan's Multiple Range Test at 5%.The results showed that the interaction bioslurry fertilizerand treatment and fertilizer N, P, K effect no significant effect on seedling height, number of leaves, stem circumference, volume root, leaf area, dry weight, and the ratio of root and crown and root dry weight. Administration of 100 ml of bioslurry fertilizerand 2 g of N, P, K is the best treatment on plant height, number of leaves, leaf area and root volume . Keywords:Bioslurry fertilizer, N, P, K and Cacao